2018
DOI: 10.5802/smai-jcm.28
|View full text |Cite
|
Sign up to set email alerts
|

Second-order entropy satisfying BGK-FVS schemes for incompressible Navier-Stokes equations

Abstract: Abstract. Kinetic BGK numerical schemes for the approximation of incompressible Navier-Stokes equations are derived via classical discrete velocity vector BGK approximations, but applied to an inviscid compressible gas dynamics system with small Mach number parameter, according to the approach of Carfora and Natalini (2008). As the Mach number, the grid size and the timestep tend to zero, the low Mach number limit and the time-space convergence of the scheme are achieved simultaneously, and the numerical visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…When the Mach number is small a well-known difficulty is to design asymptoticpreserving schemes, which means schemes that are uniformly accurate with respect to the Mach number. It has been pointed out in [7] that until now there was no asymptotic-preserving scheme which satisfies a fully discrete entropy inequality and which is first-order accurate in the low Mach number regime. Indeed a scheme proposed in [7] is entropy-satisfying and asymptotic-preserving but the order of accuracy is only 2/3 in the incompressible asymptotics.…”
Section: Application To Low Mach Number Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the Mach number is small a well-known difficulty is to design asymptoticpreserving schemes, which means schemes that are uniformly accurate with respect to the Mach number. It has been pointed out in [7] that until now there was no asymptotic-preserving scheme which satisfies a fully discrete entropy inequality and which is first-order accurate in the low Mach number regime. Indeed a scheme proposed in [7] is entropy-satisfying and asymptotic-preserving but the order of accuracy is only 2/3 in the incompressible asymptotics.…”
Section: Application To Low Mach Number Flowsmentioning
confidence: 99%
“…It has been pointed out in [7] that until now there was no asymptotic-preserving scheme which satisfies a fully discrete entropy inequality and which is first-order accurate in the low Mach number regime. Indeed a scheme proposed in [7] is entropy-satisfying and asymptotic-preserving but the order of accuracy is only 2/3 in the incompressible asymptotics. On the contrary, the Lagrange-Projection scheme proposed in [14] (see also [15]) is first-order accurate (uniformly with respect to the Mach number) but the underlying entropy inequality is no longer valid when we are too close to the asymptotic limit.…”
Section: Application To Low Mach Number Flowsmentioning
confidence: 99%
“…That means that the flux is decomposed in separated directions: ( ) = + ( ) + − ( ). We have chosen the Lax-Friedrichs decomposition in order to define Fj ± (W) (Bouchut, 2018). This will enable to import the continuous kinetic entropy condition to the discrete level.…”
Section: Discrete Schemementioning
confidence: 99%
“…As the scheme is only written in term of moments, the boundary conditions are treated as in FVM or finite difference method. For applying Dirichlet boundary conditions, we use the standard ghost cells Neumann to the other components (see Bouchut, 2018 for details).…”
Section: Adding Diffusionmentioning
confidence: 99%
“…In [13,10], it is numerically studied the convergence of the solutions to the vector BGK model to the solutions to the incompressible Navier-Stokes equations. More precisely, assuming that, in a suitable functional space, ρ ε →ρ, u ε →û, and ρ ε −ρ ε 2 →P , under some consistency conditions of the BGK approximation with respect to the Navier-Stokes equations, [13], it can be shown that the couple (û,P ) is a solution to the incompressible Navier-Stokes equations.…”
Section: Introductionmentioning
confidence: 99%